Contemporary decline in northern Indian Ocean primary production offset by rising atmospheric nitrogen deposition - Malsang, Manon; Resplandy, Laure; Bopp, Laurent; Zhao, Yangyang; Ditkovsky, Sam; Yang, Fan; Paulot, Fabien; Lévy, Marina (Frontiers in Marine Science, 2024)
Since 1980, atmospheric pollutants in South Asia and India have dramatically increased in response to industrialization and agricultural development, enhancing the atmospheric deposition of anthropogenic nitrogen in the northern Indian Ocean and potentially promoting primary productivity. Concurrently, ocean warming has increased stratification and limited the supply of nutrients supporting primary productivity. Here, we examine the biogeochemical consequences of increasing anthropogenic atmospheric nitrogen deposition and contrast them with the counteracting effect of warming, using a regional ocean biogeochemical model of the northern Indian Ocean forced with atmospheric nitrogen deposition derived from an Earth System Model. Our results suggest that the 60% recent increase in anthropogenic nitrogen deposition over the northern Indian Ocean provided external reactive nitrogen that only weakly enhanced primary production (+10 mg C.m–2.d–1.yr–1 in regions of intense deposition) and secondary production (+4 mg C.m–2.d–1.yr–1). However, we find that locally this enhancement can significantly offset the declining trend in primary production over the last four decades in the central Arabian Sea and western Bay of Bengal, whose magnitude are up to -20 and -10 mg C.m–2.d–1.yr–1 respectively.